Learning probability of 4th grade science curriculum learning outcomes among visually impaired students - Seraceddin Levent Zorluoğlu; Tuğçe Ergazi; Şeyma Eser (International Journal of Evaluation and Research in Education (IJERE), 2019)
In this study, it is aimed to evaluating of learning probability of 4th grade science course curriculum learning outcomes by visually impaired students. Therefore, ability to gain learning outcomes has been examined. In addition to, in case of gaining of learning outcomes, “how to gain?” question was investigated. Document analysis method was used for this analysis. 46 learning outcomes were analyzed through descriptive analysis. As a result of analyzing, the confidence coefficients were found to be (.72) greater than .70. From these findings, low vision students could gain 80.4% and partially gain 19.6% of learning outcomes; blind students could gain 58.7% and partly gain 26.1% and not gain 15.2% of learning outcomes. It is thought that great majority of learning outcomes can be gained by visually impaired students. Visually impaired students can gain to curriculum learning outcomes, however it is necessary to use promoters for these students during teaching.